The value of the storytelling as a teaching resource - Méndez del Portal, Rocío (2017)
The story is a didactic resource that can be used by teachers of different curricular areas because it is a flexible tool that adapts to different study contents. Likewise, it is a mean that can be used to enhance the work with values in the classroom. In addition, it promotes interactions between teachers and students because through symbols, the story is related to the feelings and emotions of their listeners or readers, which facilitates the teaching-learning process